Nexus between technological, organizational and environmental factors, digital marketing capability and performance of smes: moderation role of innovation capability - Sathana, V. (Sri Lanka Institute of Marketing, 2025)
The study aims to identify the relationship between Technological, Organizational, and Environmental factors, digital marketing capabilities, innovation capabilities, and business performance of SMEs. The quantitative approach is suitable for this study. A convenient sampling technique was applied to select respondents and sample units are the owners or managers of SMEs. A structured questionnaire was developed and delivered to 400 SMEs. Data were analyzed by using AMOS with Structural equation modeling. The findings revealed that Technological, organizational, and environmental factors significantly influence digital marketing capability, and digital marketing capability significantly impacts the performance of SMEs. Innovation capability significantly strengthens the relationship between digital marketing capability and the performance of SMEs. Digital marketing capability significantly mediated the relationship between the technological, organizational, and environmental factors and the performance of SMEs. Based on the theory of resource-based view and TOE framework, the novel model was developed with the link between TOE, DCM, and the performance of SMEs with the moderator role of innovation capability and the mediation role of DCM. SMEs should prioritize investments in digital technologies that align with their marketing objectives. Fostering a culture of continuous learning and innovation within the organization can significantly enhance digital marketing capabilities. Policymakers and industry associations should develop supportive programs and incentives to encourage technology adoption among SMEs.
Keywords: Digital marketing capabilities; Innovation capabilities; SMEs; Technological, organizational, and environmental factors